Sheep shepherds in the Algerian agro-pastoral steppes: Which reading? - Kanoun M.; Meguellati-Kanoun A.; Huguenin J.; Baiera M.; Bellahrache A.; Abdellaoui B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The shepherd remains one of the essential professions in the small ruminant breeding sector. His work plays a major role in feeding grazing animals and is an additional guarantee for food security. However, the transformation of the Algerian steppes under the joint influence of economic, territorial, agricultural and environmental policies has made it difficult to recruit shepherd by the herders. This communication presents the difficulties and challenges faced by herders in hiring a competent shepherd. Hence our questioning on the situation of shepherds and the consequences of changes in livestock farming on the future of this profession. To this end, group interviews and surveys of 100 herders were carried out in the municipality of El-Guedid-Algeria. Our analyses made it possible to obtain information characterizing the shepherd’s profession. Our results confirm the decisive role of the shepherd in herd management. Indeed, 73% of the herders surveyed used the shepherd service. Their salaries are based on the size of the herd and the farming system. They vary from 15,000 to 70,000 dinars/month (100 to 466€). Mobile shepherds receive a higher salary than sedentary shepherds. However, they considered that these salaries did not reflect the work done throughout the year (herding, night-time animal surveillance, animal care, feed distribution, etc.). It is noted that an essential prospective aspect to revalue this profession: 65% of the children of shepherds surveyed are not in favor of doing this job.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)